The Influence of Teacher Talk toward Students’ Attitude to Speak English - Ahmad Munawir (Universitas Negeri Makassar, 2017)
This research aimed at identifying the formal and interactional features of teacher talk in the classroom interaction during teaching and learning process. The research employed mixed methods research design. In this case, the researcher applied QUAN-qual model. The subjects consist of two English teachers and the fourth year students of English Education Department of Tarbiyah and Teacher Training Faculty at State Islamic University of Alauddin Makassar. The researcher collected the data using interview, questionnaire, passive participant observation which was analysed by using formal features and interactional features analysis. The research result indicated that the type token ratio of the teachers was low. It revealed that the vocabulary they used in delivering the material less varied. Then, the mean length utterance for Teacher A was 8.85 wpu and for the Teacher B was 12.06 wpu. It meant that teacher A delivered shorter utterances and Teacher B produced longer utterances. The Teacher A and B used more procedural questions than convergent and divergent questions in interacting in the classroom. The teachers provided interactional feedback when addressing students in the classroom. In terms of attitude, the students had positive attitude toward teacher talk. It was highly approved by the result of questionnaire where the students were favourable to the teacher talk. In addition, the students were motivated to speak English if the teacher encouraged them to speak English. Keywords : Influence,Teacher Talk, Students’ Attitude,Speak English